Bioesthetic outcome of immediate versus early implant placement for anterior implant supported single tooth. (Randomized Clinical Trial) - Sara El Touliani; Ahmed M. Abdelhamid; Nada M.H. Fahmy; Yasser M. Aly (Publymed, 2024)
Statement of problem: Providing a definitive anterior implant placement restoration with proper esthetic and peri implant soft tissue contour are important for both immediate and early implant placement. Purpose: Bioesthetic outcome of immediate versus early implant placement for anterior implant supported single tooth restoration used customized healing abutments in split mouth technique. Material and method: Twenty-four implants were placed in twelve patients age range between 20 and 40 years, one on each side to replace non restorable teeth in the maxillary anterior region in a split mouth technique. Extraction of one side was done for early implant placement after 4 weeks the other was extracted and both implants were inserted one side as immediate where the other is early implant placement. Customized healing abutments were fabricated using cervico mold and connected to both dental implants. After 3 month defentive crowns were inserted for both sides. The periodontal probing depth and bleeding index at 3, 6 and 12 months were evaluated. Also, pink and white esthetic score (PES-WES) was evaluated at 3,6 and 12 months after implant placement Results: The frequency percentage of probing depth decreased significantly from 3 month until 12 month after crown insertion for of immediate implant placement. When comparing between the two approaches, there was no significant difference between them. On the other hand the mean of bleeding index of both approaches are decreased significantly during 12 month period which there is insignificant difference between them. The individual parameters of PES showed significant difference between the two groups regarding soft tissue level and soft tissue curvature at the different intervals. Where the early implant placement (EIP) with customized healing abutment showed better pink esthetic score (PES) than immediate implant placement (IIP) with customized healing abutment while the white esthetic score (WES) showed no significant difference. Conclusion: Both together EIP and IIP were associated with proper periodontal health with no significant difference between them. Concerning the early implant placement that was associated with better PES than immediate implant placement while the WES showed no difference between both. Clinical implication: The use of cervico device for construction of customized healing abutments prepares soft tissue for the prosthetic stage preserving its contours and eliminating the need for reopening surgery for immediate as well as for early implant placement.